Randomized controlled study to evaluate the efficacy of adalimumab in patients with different forms of refractory uveitis - Mackensen, Friederike; Jakob, Eva; Grewing, Viviane; Lorenz, Hanns-Martin; Max, Regina; Becker, Matthias D. (Ocular immunology and inflammation, 2018)
Purpose: TNF alpha inhibitors have revolutionized the care of vision-threatening uveitis. This study evaluated the efficacy of adalimumab (ADA) for the treatment of refractory noninfectious uveitis.Design: Randomized, prospective, controlled, two-center clinical trialMethods: Patients with active uveitis despite combined oral low-dose prednisolone and immunosuppression were randomized for additional ADA with corticosteroids in a fixed tapering regime, or corticosteroids only. Primary outcome measure at three months was improved best-corrected visual acuity (BCVA; >2 lines). In case of treatment failure, switch to the other arm was possible.Results: Twenty-five patients (10 ADA, 15 controls) were included. BCVA increased with ADA by > 2 lines in 6/10 patients (60%; mean increase of 0.23 logMAR), but in only 2/15 from controls (13%, mean increase of 0.04 logMAR, Fisher´s exact test p = 0.00221).Conclusions: The results show superiority of ADA over controls in severe ocular inflammation including anterior uveitis.
Published online: 29 Dec 2017
Gesehen am 05.08.2019